2009
DOI: 10.1111/j.1754-4505.2009.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries experience in individuals with cerebral palsy in relation to oromotor dysfunction and dietary consistency

Abstract: The aim of this study was to investigate caries experience in individuals with cerebral palsy (CP) who have oromotor dysfunction and relate it to age and dietary consistency. Noninstitutionalized individuals with CP (n = 108) aged 4-19 years (mean: 10 years, 1 month +/- SD 4 years, 5 months) were recruited for this study. Subjects who were severely impaired (35.2%) had orofacial motor dysfunction most frequently, followed by those who were slightly affected (27.7%), moderately affected (20.4%), and very slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 15 publications
5
64
1
10
Order By: Relevance
“…The carious component obtained the highest value in the index in all age brackets, with a total average of 3.05 teeth attacked by caries. This result is similar to another study found in the literature [14] that compared the DMFT of children with special needs without disability, verifying a major DMFT in children from the first group. The comparison between children with and without special needs reflects the difficulty of this specific clientele to maintain good rates of oral health, as well as it reveals the difficulty of finding prevalence studies about dental caries in this population.…”
Section: Discussionsupporting
confidence: 81%
“…The carious component obtained the highest value in the index in all age brackets, with a total average of 3.05 teeth attacked by caries. This result is similar to another study found in the literature [14] that compared the DMFT of children with special needs without disability, verifying a major DMFT in children from the first group. The comparison between children with and without special needs reflects the difficulty of this specific clientele to maintain good rates of oral health, as well as it reveals the difficulty of finding prevalence studies about dental caries in this population.…”
Section: Discussionsupporting
confidence: 81%
“…Em seu estudo sobre a prevalência da cárie dentária, Santos et al 16 verificaram um maior CPO-D em crianças com necessidades especiais do que em crianças sem deficiência, devido, principalmente, à dificuldade de manutenção de uma higiene bucal satisfatória.…”
Section: Discussionunclassified
“…Table 6 shows that 80.2% of parents said that milk teeth don't require good care. 40.7% said that the media was their main source of information about oral health. About half 50.4% responded that they can maintain good dental health in their children by supervising their tooth brushing, reducing sugary food intake and making regular visits to a dentist.…”
Section: Resultsmentioning
confidence: 99%